LEARNING INNOVATION: APPLICATION OF DISCOVERY LEARNING-BASED WORKSHEETS TO SHARPEN STUDENTS’ COLLABORATION SKILLS ON HYDROELECTRIC POWER PLANTS - Ihza Rizky Winedar; Habibatul Unayah; Muhammad Rasyid; Jumadi Jumadi; Sabar Nurohman (Jurnal Eduscience)
Purpose—In the 21st century, where education emphasizes the development of holistic competencies, collaboration skills have become an important aspect of preparing students to face the complex demands of the real-world environment. This study aims to analyze the effect of discovery learning on improving students' collaboration skills in studying alternative energy sources, mainly hydropower.